Treatment of 4T1 Metastatic Breast Cancer with Combined Hypofractionated Irradiation and Autologous T-Cell Infusion - Filatenkov, Alexander (2014)
The goal of this study was to determine whether a combination of local tumor irradiation and autologous T-cell transplantation can effectively treat metastatic 4T1 breast cancer in mice. BALB/c mice were injected subcutaneously with luciferase-labeled 4T1 breast tumor cells and allowed to grow for 21 days, at which time metastases appeared in the lungs. Primary tumors were treated at that time with 3 daily fractions of 20 Gy of radiation each. Although this approach could eradicate primary tumors, tumors in the lungs grew progressively. We attempted to improve efficacy of the radiation by adding autologous T-cell infusions. Accordingly, T cells were purified from the spleens of tumor-bearing mice after completion of irradiation and cryopreserved. Cyclophosphamide was administered thereafter to induce lympho-depletion, followed by T-cell infusion. Although the addition of cyclophosphamide to irradiation did not improve survival or reduce tumor progression, the combination of radiation, cyclophosphamide and autologous T-cell infusion induced durable remissions and markedly improved survival. We conclude that the combination of radiation and autologous T-cell infusion is an effective treatment for metastatic 4T1 breast cancer.